Design and equipment for restaurants and foodservice : a management view / Costas Katsigris, Chris Thomas - Katsigris, Costas
"From the decor that helps define the customer's experience, to the steps taken to comply with workplace safety and health regulations, to the capital investments in major equipment, a well-designed foodservice facility blends many different elements into a functional and pleasing whole. Decision-makers who understand these different elements and how they work together will reap the plentiful rewards that come from good design choices in a restaurant or foodservice endeavor. Design and Equipment for Restaurants and Foodservice, Third Edition takes a comprehensive approach to planning and developing a restaurant or foodservice space. This "go-to guide"encompasses everything from creating a restaurant concept to maintaining a commercial-grade oven, and is unique in its attention to both the front and back of the house. Revised and updated with the latest foodservice industry trends, this new Third Edition features: New and expanded coverage of green design, including energy and water use, recycling and waste streams, smarter use of space, and LEED "green building" principles New information on technology use in foodservice Coverage of design in the context of industry trends including mobile foodservice, multichain operators, branding concepts, design for smaller spaces, and integrating cook-chill methods for quality control Recent developments in equipment technology and equipment purchasing, financing, leasing, and insuring The latest updates on topics including sanitation practices, healthier cooking oils, and regulations such as the Americans with Disabilities Act Clearly organized for learning, and full of such resources as callout boxes, interviews with industry experts, take-away points, and other helpful features, Design and Equipment for Restaurants and Foodservice, Third Edition gives hospitality industry students and working professionals a complete guide to this essential subject."--Publisher's website.